THE RELATIONSHIP BETWEEN ANXIETY WITH QUALITY OF LIFE ELDERLY SUFFERING FROM HYPERTENSION AT PUSKESMAS BABADAN PONOROGO - Iswatun, Iswatun; Lutfiandini, Cherlys Tin; Wijayanti, Endah Sri; Umam, Khotibul; Sairozi, Ali; Susanto, Joko; Rindayati, Rindayati; Okviasanti, Fanni (Universitas Airlangga, 2024)
Introduction: Quality of life is a person's perception of the physical, psychological, social, and environmental conditions in life. Quality of life is impacted by excessive anxiety about health conditions one of them hypertension. The creasing of age and hypertension experienced elderly trigger other diseases. This study aims to determine the relationship between anxiety and quality of life in elderly people with hypertension. Methods: The research design uses quantitative with a cross-sectional study. The inclusion criteria were elderly people with high blood pressure â‰¥140/90 mmHg. Sampling was carried out using a purposive sampling technique, totaling 160 samples. The instruments used were the GAI and OPQOL-BRIEF questionnaires. Statistical test with Spearman Rank (Rho). Results: For more than half of the total sample, elderly anxiety was in the moderate category (63.1%) and most of the elderly's quality of life was in the poor category (80.8%). The statistical test results showed a significance of 0,000 because Ï < 0.05, it was concluded that there was a significant relationship between anxiety and quality of life in elderly people with hypertension at Puskesmas Babadan Ponorogo. The closeness is relationship 0.699 considered strong. Conclusions: There is a relationship between anxiety and quality of life in elderly people with hypertension at Puskesmas Babadan Ponorogo. It is hoped that respondents can improve their healthy lifestyle, have regular health check-ups, and not feel excessively anxious about their health